2023
DOI: 10.1093/mnras/stad1961
|View full text |Cite
|
Sign up to set email alerts
|

X-ray polarimetry of X-ray pulsar X Persei: another orthogonal rotator?

Abstract: X Perseiis a persistent low-luminosity X-ray pulsar of period of ≈ 835 s in a Be binary system. The field strength at the neutron star surface is not known precisely, but indirect signs indicate a magnetic field above 1013 G, which makes the object one of the most magnetized known X-ray pulsars. Here we present the results of observations X Persei performed with the Imaging X-ray Polarimetry Explorer (IXPE). The X-ray polarization signal was found to be strongly dependent on the spin phase of the pulsar. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The Imaging X-ray Polarimetry Explorer (IXPE; Weisskopf et al 2022) provides a unique opportunity to probe the X-ray polarization of XRPs. So far, the detection of phase-averaged/ resolved polarized emission in a handful of XRPs, such as Her X−1 (∼10%; Doroshenko et al 2022), Cen X−3 (∼5.8%; Tsygankov et al 2022), 4U 1626 − 67 (∼4.8%; Marshall et al 2022), Vela X−1 (∼2.3%; Forsblom et al 2023), GRO J1008 − 57 (∼15%; Tsygankov et al 2023), EXO 2030 + 375 (∼3%; Malacaria et al 2023), X Persei (∼20%; Mushtukov et al 2023), and GX 301 − 2 (∼3%-10%; Suleimanov et al 2023) is confirmed with IXPE. If not all, most of the sources show a "low" polarization degree (PD) compared to the predictions from the existing models (Meszaros et al 1988;Caiazzo & Heyl 2021a, 2021b, and its cause remains an open question to date.…”
Section: Introductionmentioning
confidence: 99%
“…The Imaging X-ray Polarimetry Explorer (IXPE; Weisskopf et al 2022) provides a unique opportunity to probe the X-ray polarization of XRPs. So far, the detection of phase-averaged/ resolved polarized emission in a handful of XRPs, such as Her X−1 (∼10%; Doroshenko et al 2022), Cen X−3 (∼5.8%; Tsygankov et al 2022), 4U 1626 − 67 (∼4.8%; Marshall et al 2022), Vela X−1 (∼2.3%; Forsblom et al 2023), GRO J1008 − 57 (∼15%; Tsygankov et al 2023), EXO 2030 + 375 (∼3%; Malacaria et al 2023), X Persei (∼20%; Mushtukov et al 2023), and GX 301 − 2 (∼3%-10%; Suleimanov et al 2023) is confirmed with IXPE. If not all, most of the sources show a "low" polarization degree (PD) compared to the predictions from the existing models (Meszaros et al 1988;Caiazzo & Heyl 2021a, 2021b, and its cause remains an open question to date.…”
Section: Introductionmentioning
confidence: 99%